Isolation and Characterization of Protoplasts from Saccharomyces rouxii - Arnold, Wilfred N. (1979)
Cells of the osmotolerant yeast Saccharomyces rouxii were transformed to protoplasts in good yield (85%) by digesting cell walls with snail-gut enzyme in the presence of 10 mM dithioerythritol, 0.1 M sodium phosphate buffer (pH 6.8), and 2.0 M KCl. The requirement for 2.0 M KCl compares with that for S. bisporus var. mellis (another osmotolerant species) and contrasts with the 0.3 to 0.8 M KCl concentrations used in the preparation of most yeast protoplasts. Short digestions (60 min or less) produced mostly spheroplasts; longer incubations (90 min or more) yielded mostly protoplasts as judged by electron micrographs. These protoplasts could be transferred to 1.0 M KCl or 2.0 M sorbitol without lysing, but lysis was pronounced in 0.5 M KCl or 1.0 M mannitol and complete in 0.02 M KCl. Protoplasts were separated from isolated cell wall remnants and debris by centrifugation on a linear gradient of Ficoll 400 (35 to 17.5%, wt/vol) containing 2.0 M KCl. Both crude and fractionated protoplast preparations contained vesicles which were identified with the periplasmic bodies of whole cells. Some of the periplasmic bodies were connected to protoplasts by fine pedicels; others appeared free. Independent degeneracy of periplasmic bodies was occasionally observed. β-Fructofuranosidase (EC 3.2.1.26) activity is cryptic (physically) in cells of S. rouxii in contrast to the expressed enzyme (periplasmic space) of other Saccharomyces species. This enzyme remains cryptic in protoplast preparations of S. rouxii but is expressed upon lysis. The same specific activities were found per unit cell or protoplast. The possible association of the cryptic enzyme with periplasmic bodies is discussed.